2022
DOI: 10.3390/agronomy12020471
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impacts of Different Cropping Patterns on Soil Physico-Chemical Properties and Enzyme Activities in the Low Land Plain of North China

Abstract: Various cropping patterns are extensively used on the North China Plain, which greatly alter various soil properties. Although these soil properties respond differently to the different cropping patterns, little is known about the possible effects of cropping patterns on desalinized soils. To assess the effects of the different cropping patterns on soil properties and enzyme activities, a long-term field experiment was conducted at the Nanpi Agro-Ecological Station in Hebei Province, China. The cropping patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Soil physicochemical characteristics can evaluate soil quality. The tillage practices ( Coulibaly et al, 2022 ), straw return ( Huang et al, 2021 ), fertilization practices ( Zhao et al, 2021 ), and cropping patterns ( Gikonyo et al, 2022 ) can significantly affect soil physicochemical properties. Increasing the content of effective soil N, P and K can improve crop yield ( Gondwe et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil physicochemical characteristics can evaluate soil quality. The tillage practices ( Coulibaly et al, 2022 ), straw return ( Huang et al, 2021 ), fertilization practices ( Zhao et al, 2021 ), and cropping patterns ( Gikonyo et al, 2022 ) can significantly affect soil physicochemical properties. Increasing the content of effective soil N, P and K can improve crop yield ( Gondwe et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…10.3389/fmicb. 2022.1024686 Frontiers in Microbiology 09 frontiersin.org (Huang et al, 2021), fertilization practices (Zhao et al, 2021), and cropping patterns (Gikonyo et al, 2022) can significantly affect soil physicochemical properties. Increasing the content of effective soil N, P and K can improve crop yield (Gondwe et al, 2020).…”
Section: Iscm Improves the Soil Nutritionmentioning
confidence: 99%
“…The previous cropping history with the V. dahliae host and non-host affected the ID of the pathogen in the soil not only through its direct influence, but also through its influence on the physicochemical properties of the soil. The Mg exchange values were higher in the fields with the very favourable history than the barely favourable previous cropping history fields in the Iberian Peninsula, as well as in the fields with spring cotton (one of the most common host crops of V. dahliae in the favourable treatment) compared to spring maize single-cropping patterns for ten years in North China [ 26 ]. In addition, the Na exchange increased in the fields when the hosts of V. dahliae were cropped for four out of the five previous years (favourable treatment) in this study and when sugar beet (a host crop of V. dahliae employed in the very favourable cropping history group of this study) was intercropped with maize for five consecutive years in the Dura sub-catchment, northern Ethiopia [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different typical and beneficial crop planting patterns have a positive impact on soil properties [31], such as increasing OM content [32,33]. Gikonyo et al (2022) reported that the winter wheatsummer maize planting rotation had higher soil OM than other crop planting patterns [34]. Furthermore, the melon-cowpea intercropped system showed significantly increased TN, AP, and OM levels [35].…”
Section: Effects Of Different Crop Planting Patterns On Soil Chemical...mentioning
confidence: 99%